PROJECT MANAGEMENT PEDAGOGY: CULTIVATING CRITICAL THINKING SKILLS IN HIGHER EDUCATION - Sonny Gad Attipoe (Novìtnâ Osvìta, 2024)
The present study explores the integration of critical thinking skills concepts in agricultural project management instruction at the undergraduate level, using the traditional classroom theoretical approach and a blended learning model. The study, encompassing 118 undergraduate students, compares the effectiveness of these methods in enhancing students' understanding, measured through examination scores, group presentations, and students’ overall perceptions of the use of the methods. Students achieved a mean examination score of 64.82% under the traditional approach and 72.66% for the blended learning approach. Statistical analysis, including a t-test, revealed significant differences favoring the blended approach. Additionally, performance assessments using six criteria during presentations yielded varied mean scores. ANOVA analysis showed a significant difference among the groups, and post hoc tests highlighted distinctions between specific groups’ means, emphasizing the effectiveness of blended learning in enhancing students understanding. Students' perceptions, gathered through a 5-point Likert scale, underscored satisfaction with the blended approach due to its flexibility, catering to diverse learning styles, and fostering critical thinking skills. We recommend institutions strengthen project management instruction by adopting blended learning, emphasizing critical thinking, and prioritizing continuous assessment and student-centric approaches since they cultivate an engaging learning experience, preparing students for managing future complexities on projects.